Whole-body cold water immersion as a recovery tool in elite olympic weightlifters - Schimpchen, J.; Wagner, M.; Meyer, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Training and/or competing multiple times per day often induces excessive amounts of stress in athletes. This might result in temporary impairments in performance due to a variety of factors. Hence, the aim of the study was to investigate whether whole-body cold water immersion following intensive training sessions can be a useful recovery tool for elite Olympic weightlifters. Methods: Seven male members (25 ± 4 y) of the German national Olympic weightlifting team participated in the study. A randomized cross-over design was employed, consisting of two four day phases separated by a ten day wash-out period. In both phases, athletes underwent a total of five high-intensity training sessions, which were immediately followed by either a cold water immersion protocol (CWI) or a control protocol (CON). CWI consisted of a single bout of 10 consecutive minutes, during which the athletes were seated and immersed up to their neck in water at between 12°-15° C, while CON consisted of 10 min of passive recovery in the same body position. A snatch pull movement at 85% and 90% of each athlete`s individual snatch 1 RM served as a sport-specific performance test and was executed before and after both phases. Maximal barbell velocity during the pull was recorded. Throughout data collection, venous blood samples were collected from the athletes and subjective ratings of general physical and mental fatigue and recovery were assessed using a questionnaire. Results: Physical performance at either snatch pull intensity (85% 1RM: P=0.94; 90% 1RM: P=0.25) did not differ significantly between CWI and CON (condition x time). While questionnaires revealed a significant decline in ratings of overall recovery (P<0.001) and a significantly higher rating of overall stress (P=0.03) over time, there were no significant differences between conditions (P=0.14; P=0.98). Similarly, neither of the analyzed blood parameters changed significantly between conditions over time (CK: P=0.53; Urea: P=0.43; Cortisol: P=0.59; Testosterone: P=0.53; T:C ratio: P=0.69). On an individual level, responses to CWI varied considerably between subjects. Conclusions: In general, CWI did not prove to be an effective tool to enhance recovery in elite Olympic weightlifters over a three day intensive training period. However, even though the group was rather homogeneous with regard to performance, there were considerable inter-subject differences in their response to CWI. While some athletes improved performance and subjective well-being, others saw a decline in both parameters. Based on this data, it seems difficult to generalize the usefulness of CWI even within a homogenous athletic population. It appears that athletes are best advised on a case-by-case basis.